ANALISA PERINGKAT OBJEK WISATA DI KABUPATEN KUNINGAN MENGGUNAKAN METODE PREFERENCE RANGKING ORGANIZATION METHODE FOR ENRICHMENT EVALUATION - Aah Sumiah (NUANSA INFORMATIKA, 2014)
ABSTRAKÂ Assessment of tourism object is a process where the Department of Kuningan tourism and culture can evaluate and decide easily its rank based on some criterias in the tourism object. It can give information to society about the tourism object relating to its quality and facility. So it is necessary to facilitate the development of information technology in assessing tourism system. One of information technology is Decision Support System ( DSS ). Decision Support System is a set computer based procedure for processing and assessment to help managers to make decisions. Decision-makin in this case is to help decision makers to choose various alternative decision as the result of information processing that is obtained or available. The writer uses Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) because this method is one method of solving problems withÂ  priority level. The result of this research is hoped that it can help Department of Kuningan Tourism and Culture in assessing all tourism objects.Keywords : tourism object , Promethee , information technology, Decision Support System,